Opportunism and Opportunity Cost as Antecedents of Participatory Behavior - Lee, Junesoo; Choi, Heung-Suk; Han, Seungjoo (Annals of Social Sciences & Management Studies, 2020)
Despite its positive impacts, public participation often begets a representativeness problem due to participants’ opportunism and opportunity cost. Using the survey on 2,000 citizens in South Korea, the research results show that: (1) citizens’ opportunism in terms of self-interest or free-riding may significantly influence their participatory behaviors and (2) citizens’ opportunity costs may act as a mediating factor, i.e., a higher opportunity cost lessens the impact of opportunism on participation. The findings imply that a desirably represented citizen participation can be supported by considering and mobilizing (not manipulating) citizens’ sense of opportunism and opportunity cost.